Study of the effect of dicumyl peroxide on morphological and physical properties of foam injection molded poly(lactic acid)/poly(butylene succinate) blends - J. F. Campuzano; I. D. Lopez (eXPRESS Polymer Letters, 2020)
Blends of poly(lactic acid) (PLA) with poly(butylene succinate) (PBS) were compounded in the presence of dicumyl peroxide (DCP) to improve the compatibility and foaming capabilities. PLA/PBS blends with a weight ratio of 40/60 and DCP contents of 0, 0.1, 0.4 and 1 wt% were analyzed. Blends and neat materials were foam injection molded using azodicarbonamide as a chemical foaming agent. The thermal and rheological behaviors of materials are discussed. The morphologies and mechanical responses of the foamed samples are compared and analyzed. The best blend results were obtained with 0.1 wt% of peroxide, reaching impact strength values similar to those of neat-foamed PBS and cell population densities higher than neat PLA. Peroxide contents higher than 0.4 wt% tend to decrease the performance of the blend due to excessive crosslinking.